Optimized Method of Extracting Rice Chloroplast DNA for High-Quality Plastome Resequencing and de Novo Assembly - Takamatsu, Takeshi; Baslam, Marouane; Inomata, Takuya; Oikawa, Kazusato; Itoh, Kimiko; Ohnishi, Takayuki; Kinoshita, Tetsu; Mitsui, Toshiaki (Frontiers in Plant Science, 2018)
Chloroplasts, which perform photosynthesis, are one of the most important organelles in green plants and algae. Chloroplasts maintain an independent genome that includes important genes encoding their photosynthetic machinery and various housekeeping functions. Owing to its non-recombinant nature, low mutation rates, and uniparental inheritance, the chloroplast genome (plastome) can give insights into plant evolution and ecology and in the development of biotechnological and breeding applications. However, efficient methods to obtain high-quality chloroplast DNA (cpDNA) are currently not available, impeding powerful sequencing and further functional genomics research. To investigate effects on rice chloroplast genome quality, we compared cpDNA extraction by three extraction protocols: liquid nitrogen coupled with sucrose density gradient centrifugation, high-salt buffer, and Percoll gradient centrifugation. The liquid nitrogen – sucrose gradient method gave a high yield of high-quality cpDNA with reliable purity. The cpDNA isolated by this technique was evaluated, resequenced, and assembled de novo to build a robust framework for genomic and genetic studies. Comparison of this high-purity cpDNA with total DNAs revealed the read coverage of the sequenced regions; next-generation sequencing data showed that the high-quality cpDNA eliminated noise derived from contamination by nuclear and mitochondrial DNA, which frequently occurs in total DNA. The assembly process produced highly accurate, long contigs. We summarize the extent to which this improved method of isolating cpDNA from rice can provide practical progress in overcoming challenges related to chloroplast genomes and in further exploring the development of new sequencing technologies.